Sampling Deviation Real-time Calibration Method for Wideband Simulator - Song Bingbing; Pan Minghai; Hu Xiaohua (Universitas Ahmad Dahlan, 2015)
Hardware-in-the-loop simulation is an efficient method for research on radar system.Target’s echo which offered by the simulator should be synchronized with radar on frequency, time, and range bin. However, because simulator needs to take into account of the requirements of various types of radar, it is difficult to make the clock of simulator synchronized with the clock of radar. To solve the problem, synchronous sampling deviation model is established. Influence of sampling deviation on imaging is analyzed. An engineering method is put forward to eliminate the sampling deviation. This method not only provides a reference for simulation system, but also provides a reference for the design of radar system.